Gender Differentiation in Classroom Interaction: A Critical Discourse Analysis of Teacher–Student Talk - Leli Ridayani; Wahyudi Badri; Dian Susyla (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates gender-based discourse patterns in English classrooms through Critical Discourse Analysis (CDA) at MTsN 2 Kota Bengkulu during the 2024/2025 academic year. The participants were 8th grade students whose classroom interactions were recorded, transcribed, and analyzed using Fairclough’s CDA framework. The study aimed to identify (1) how male and female students participated in classroom discourse and (2) what gendered patterns emerged during teacher–student and student–student interactions. The findings revealed that male students dominated verbal participation by taking more turns, providing longer responses, and initiating more spontaneous interactions. Female students participated less frequently and tended to wait for teacher nomination before speaking, producing shorter and more cautious responses. Teachers’ discourse practices, including question distribution and feedback patterns, unintentionally reinforced these differences by giving male students more opportunities for elaboration. The results align with previous research, indicating that classroom discourse often reproduces broader gender ideologies. The study concludes that English classrooms at MTsN 2 Kota Bengkulu reflect gendered participation norms and recommends more equitable discourse strategies to promote balanced interaction. Keywords: Critical Discourse Analysis, gender, classroom discourse, participation, EFL learners